PERLINDUNGAN HUKUM TERHADAP NASABAH PT.BANK RAKYAT INDONESIA UNIT AMPERA DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Erni Dwita Silambi (Universitas Musamus,Merauke,Papua, 2013)
This study aimed to consumer protection to bank customers as consumers intended for customers so that customers have the right to use the forum for customer complaints and mediation to resolve disputes in the banking sector in a simple, easy and cepat.Metode used in this study by the research adalalah dilaksanakn field at PT Bank BRI unit Ampera and the literature study conducted through reading books that deals with the writing of the journal, the statements derived from the literature as well as legal issues articles. This research was conducted using qualitative descriptive, using data collection techniques derived from secondary data is the primary legal materials, secondary, tertiary, and secondary data to support the use interview techniques to the employees and customers of the bank. The results showed that in the settlement between the bank and the customer will be settled amicably between the bank and the customer, and if proven to exist error, the bank will change and if the loss can not be resolved by the bank it will be taken by way of mediation.